Material characterisation of lightweight disc brake rotors. (July 2018) - Alnaqi, Abdulwahab A; Kosarieh, Shahriar; Barton, David C; Brooks, Peter C; Shrestha, Suman
Alumina coated lightweight brake rotors were investigated to evaluate the effect of coating properties on their friction performance and thermal durability. An alumina ceramic coating on AA6082 aluminium alloy (Al-Alloy) and on 6061/40SiC aluminium metal matrix composite (Al-MMC) prepared by plasma electrolytic oxidation was studied using a programme of brake dynamometer and material characterisation tests. The results showed that the plasma electrolytic oxidation alumina layer adhered well to the Al-alloy substrate and was more uniform and durable when compared to that on the aluminium metal matrix composite. The plasma electrolytic oxidation layer significantly improved the hardness of the rotor surface for both Al-alloy and aluminium metal matrix composite substrate. The coated Al-alloy disc brake rotor was demonstrated to give good thermal and friction performance up to high rubbing surface temperatures of the order of 550 ℃, but the rotor eventually failed due to temperature build-up at a critical location.